Employee Performance Management in Actualizing Company Effectiveness at the AMPHURI Cooperative - Ramadhan, Fitrah; Zen, Muhamad (Fakultas Dakwah dan Komunikasi Universitas Islam Negeri Walisongo Semarang, 2021)
Each company certainly has its own target, as well as the AMPHURI Cooperative. The effectiveness of the cooperative is very dependent on the performance of employees, both leaders and subordinates and all scopes of work, for that, need a concept of rules that regulate all scopes of work, and also a harmonious relationship between all parties is needed. company.This research is a qualitative research, by collecting data from several ways, namely interviews, observations, and from books that can support the completeness of this data. Based on the results of the author's research, the concept of employee performance management of the AMPHURI Cooperative has been carried out well and the achievement of the company's targets has also been running effectively, as can be seen from the percentage increase in the number of umrah pilgrims in the consortium and also the increase in the number of new members of the AMPHURI cooperative each period.